Dogdog Lojor in The Seren Taun of Kasepuhan Sinar Resmi: Symbolic and Functional Analysis in the Context of Local Culture - Aria, Aria (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2025)
This study explores the symbolism and socio-cultural functions of Dogdog Lojor, a traditional Sundanese musical instrument that plays a vital role in the Seren Taun ceremony at Kasepuhan Sirna Resmi. The primary objective of this research is to analyze the symbolic meanings, as well as the social, spiritual, and ecological functions of Dogdog Lojor within the cultural framework of the Sundanese indigenous community, while also examining the challenges of its preservation amid modernization and cultural commodification. This research employs a descriptive qualitative approach, utilizing literature review, documentation, and thematic analysis of cultural texts and customary documents. The findings reveal that Dogdog Lojor serves not only as a ritual musical instrument but also as a cosmological symbol representing harmony between humans, nature, and ancestors. Its social function is evident in its role as a unifying force within the community and as a medium for informal cultural education. Furthermore, the use of natural materials and its eco-cultural production practices highlight the instrument’s contribution to environmental preservation. However, the study also identifies a shift in meaning caused by globalization pressures and a weakening of cultural regeneration among younger generations. Therefore, preserving Dogdog Lojor requires participatory, community-based strategies that respect its spiritual and symbolic context. This research is expected to contribute to the development of symbolic anthropology, ethnomusicology, and cultural ecology theories, as well as serve as a foundation for sustainable cultural preservation policies.